Optimization of public building glazing according to energy efficiency criteria - Kosenko, Leonid; Koval, Olena; Yurchenko, Yevhenii; Koval, Artem; Hryshyn, Serhii (Technology audit and production reserves, 2025)
The object of research is a two-story office building. One of the problem areas in building envelopes is stained glass structures that do not meet modern energy efficiency requirements and have significant heat loss. The research aims to develop optimal design solutions for modernizing existing glazing, aimed at reducing heat loss while preserving the architectural appearance of the facade and the economic feasibility of implementing thermal renovation measures. The research used a set of methods, namely the creation of a BIM model of the building, analysis of the thermal insulation properties of building envelopes, technical and economic comparison of thermal renovation options, and online calculation tools from window companies. The research results provided indicators of heat loss through the stained glass windows of the existing system and the proposed reconstruction options, as well as the amount of solar gain. Three options for replacing the stained glass windows were developed. One option involved the use of Rehau SYNEGO® MD-80 with 490 mm mullions and a reduction in the area of translucent structures. The heat loss savings are 56%, and the implementation cost is 3084 EUR, which is an acceptable indicator among the options considered. This is because the proposed option meets energy efficiency requirements and also takes into account the customer’s restrictions on changing the architectural appearance of the facade by no more than 50%. The proposed approach allows for a comprehensive assessment of the impact of the proposed measures on the energy balance of the building, taking into account architectural constraints and justifying an economically viable solution. Compared to traditional solutions for replacing stained glass windows based solely on thermal conductivity or standard facade solutions without taking into account the conditions of a specific object. The results obtained can be used for implementation in similar objects in public and office buildings during reconstruction or new construction.